Rebellion as Resistance: Exploring the Intersection of Individual Identity and Social Hierarchy in Anita Desai’s and Mulk Raj Anand’s Narratives - Patro, Aruna Kumar; Swain, Shishir Kumar; Pradhan, Rabindra Kumar (Mindscape: A Journal of English & Cultural Studies, 2024)
This paper examines the theme of rebellion as resistance in the works of Anita Desai and Mulk Raj Anand, focusing on the intersection of individual identity and social hierarchy. By exploring their narratives, this study highlights how both writers depict rebellion as a response to systemic oppression and cultural constraints. Desai’s characters often engage in psychological resistance against gendered expectations, while Anand’s protagonists actively challenge caste and class structures. Through a comparative analysis, this paper argues that rebellion in these texts is not merely an act of defiance but a negotiation of selfhood within socio-political constraints. Drawing from postcolonial theory, feminist critique, and subaltern studies, this research situates their works within broader literary and socio-cultural discourses on resistance. Desai’s protagonists often experience rebellion as an internal struggle against societal expectations. In Cry, The Peacock, Maya’s descent into psychological turmoil represents an unarticulated resistance to patriarchal oppression. Anita Desai brought into light the psychological oppression and gendered subjugation. Anita Desai’s works, particularly Cry, The Peacock and Clear Light of Day, illustrate the internalization of victimhood. Internalization of victimhood springs from a sensitive source which the woman especially knows, mostly her near and dear ones.